2018
DOI: 10.15201/hungeobull.67.3.4
|View full text |Cite
|
Sign up to set email alerts
|

The The impact of territorial policies on the distribution of the creative economy: tracking spatial patterns of innovation in Slovenia

Abstract: The creative economy as an alternative pathway for industrial decline was first introduced into practice in metropolitan regions of the Global North. Since then, it has gradually spread out to other highly urbanized areas of the Global South and transitional areas such as post-socialist European countries. Numerous studies tried to explain structural conditions and suggested policies to attract, retain and release creative potentials. However, the focus on promotion of the creative economy is still on large ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 46 publications
1
7
0
1
Order By: Relevance
“…Authors also pointed out the growing dynamism of the periurban zone (suburbs) where properties are significantly cheaper than in the city proper. In the present theme issue Kozina, K. and Bole, D. (2018) also clearly demonstrate the correlation between the position of a city in urban hierarchy and the weight of creative economy on the example of Slovenia. Thus, irrespective of the legacies of state-socialism the urban geography of the creative economy follows basically similar patterns in the Eastern and Western parts of Europe.…”
Section: The Urban Bias Of Creative Activitiessupporting
confidence: 54%
“…Authors also pointed out the growing dynamism of the periurban zone (suburbs) where properties are significantly cheaper than in the city proper. In the present theme issue Kozina, K. and Bole, D. (2018) also clearly demonstrate the correlation between the position of a city in urban hierarchy and the weight of creative economy on the example of Slovenia. Thus, irrespective of the legacies of state-socialism the urban geography of the creative economy follows basically similar patterns in the Eastern and Western parts of Europe.…”
Section: The Urban Bias Of Creative Activitiessupporting
confidence: 54%
“…This sparks interesting research questions for the future: is peripherality a factor that made industrial towns more resilient, because they were forced to reinvent their economies in order to survive the restructuring after the 1990s? We can confirm that those towns have a strong "pioneering spirit" (Harfst et al, 2018), exhibited through high concentrations of patents on innovations (Kozina and Bole, 2018). The case of Jutland -an industrial, successful and peripheral region in Denmark -showcased how entrepreneurs were required to be more technologically advanced, innovative and internally organised to compete with the economies of metropolitan areas (Hansen, 1991).…”
Section: Territorial Perspectives Of Small Industrial Town Typesmentioning
confidence: 57%
“…In line with these principles, smaller towns as well as completely rural areas began industrialising with factories, which is still characteristic today and explains the wide territorial distribution of industrial towns. Regional centres and older industrial towns experienced stagnation, while a completely new industry began developing in smaller towns, which became the prominent feature of the Slovene urban system (Vrišer and Rebernik, 1993;Kozina and Bole, 2018). Although many small towns subsequently changed to a service-orientated economic base (Bole, 2012), small industrial towns remain widespread and vibrant.…”
Section: Territorial Perspectives Of Small Industrial Town Typesmentioning
confidence: 99%
“…For example, Bontje et al (2011) and Marková (2014) observed that creative clusters established in this part of Europe are geared towards financial assistance from OP. Jurene and Jureniene (2017) and Kozina and Bole (2018) pointed out that creative clusters are established in the largest urban centres, and Kuleva (2018) noted that creative clusters in Russia are constantly seeking the interest of local authorities. In turn, the review by Bialic-Davendra et al (2016) confirmed that creative clusters are formed in the region's largest cities.…”
Section: Discussionmentioning
confidence: 99%